BLUE ECONOMY GOVERNANCE: THREAT LANDSCAPES IN COASTAL ECOSYSTEMS AND IMPLICATIONS FOR THE GLOBAL SOUTH - Ifegwu-Livingrich, Prince Ezeikpe; Rimamchaten, Adamu Lawi (African Journal of Social and Behavioural Sciences, 2025)
The growing relevance of the marine and blue economy has intensified global concern over the governance of coastal ecosystems, particularly in the Global South, where ecological fragilities intersect with developmental pressures. This study interrogates how evolving threat landscapes, ranging from coastal degradation and illegal fishing to marine pollution, climate-induced risks, and persistent governance deficits, undermine the sustainability of blue economy initiatives and their implications for sustainable development. The analysis draws on 62 carefully selected materials, including national policy documents, international conventions, and peer-reviewed empirical studies, chosen through relevance-based inclusion criteria. Anchored on environmental governance theory and Political Ecology, the objectives of the study are to: (1) identify main ecological and security threats affecting coastal regions; (2) assess existing blue economy governance frameworks; and (3) determine their effectiveness in promoting sustainability. Findings reveal that weak regulatory institutions, fragmented governance, and overextraction of marine resources undermine blue economy outcomes. This is exemplified by Ghana’s marine fisheries sector, which continues to experience stock depletion due to illegal, unreported, and unregulated (IUU) fishing, despite existing regulatory instruments, reflecting a wider regional governance gap. The study concludes that realising a resilient and sustainable blue economy requires coherent and adaptive governance systems supported by strengthened institutional capacities. Accordingly, the study prioritises three strategic actions: (1) establishing integrated and enforceable multi-actor maritime governance mechanisms; (2) investing in climate-resilient coastal infrastructure and ecological restoration; and (3) promoting community-based resource management alongside enhanced South–South cooperation to improve knowledge sharing and regulatory innovation.